Mental Health Issues of Women After Release From Jail and Prison: A Systematic Review. (3rd May 2016) - Stanton, Ann E.; Kako, Peninnah; Sawin, Kathleen J.
Abstract : The aim of this review article is to gain an understanding of the mental health issues of women released from jail or prison. Thirty-six studies were synthesized using the biopsychosocial model. Results indicate that released women's mental health issues include psychiatric diagnoses, psychological trauma, substance use disorders; access to psychological medications and services; and motherhood challenges, support, access to basic needs, and criminalized behaviors. Nurses can promote released women's mental health through pre-release assessment and treatment of mental health issues and ensuring access to post-release resources.  Future research should examine released women's mental health experiences.